Impact of estradiol cypionate prior to TAI and progesterone supplementation at initial diestrus on ovarian and fertility responses in beef cows - Martins, T. (2017)
In cattle, early diestrus progesterone (P4) supplementation modulates endometrial function to exert pro and anti-pregnancy establishment effects; specifically, P4 stimulates conceptus growth, but also induces early onset of luteolysis. This paradoxical effect is frequently related to the inconsistent fertility outcomes that result from P4 supplementation experiments. Aim was to investigate the impact of exogenous estradiol (E2) treatment at the end of timed fixed AI (TAI) on frequency of early luteolysis and pregnancy of beef cows supplemented with P4. Ovulations (DO of study) of suckled multiparous (n = 643) and primiparous (n = 193) Nelore cows (Bos indices) were synchronized with an E2/P4-based protocol for TAI and assigned to receive 1.0 mg of estradiol cypionate (CP) or nothing (NoCP) on D-2 and 150 mg of injectable long-acting P4 (iP4) or Placebo (NoiP4) on D4 on a 2 x 2 factorial arrangement. On D15, the iP4 supplementation increased (P < 0.05) the frequency of early luteolysis (NoCP + iP4: 26.0%; [13/50] vs. NoCP: 8.0% [4/50]), but CP prevented this effect (CP + iP4: 8.3% [4/48] and CP: 6.4% [3/471). The CP improved pregnancy/AI (P/AI) of multiparous (CP: 51.6% [165/320] and NoCP: 35.0% [113/323]; P < 0.001) and primiparous cows (CP: 40.4% [40/99] and NoCP: 24.5% [23/94], P < 0.05), regardless of iP4 treatment. The iP4 supplementation affected P/AI of CP and NoCP treated cows according to follicle size at TAI. For the CP treated cows, the iP4 supplementation improved P/AI of sub-populations of cows with follicles <12.35 mm (42.0% [34/81] vs. 53.1% [34/64]), while for NoCP treated cows, the improvements occurred in subpopulations of cows with follicles >= 12.35 mm (46.1% [35/76] vs. 58.7% [37/63]). In conclusion, strategies associating E2 and P4 supplementation decrease the incidence of early onset of luteolysis and improve P/AI of suckled beef cows with smaller follicles. (C) 2017 Elsevier Inc. All rights reserved.